Detection of Leptospira in Small Mammals at Bako National Park - Jasmin, Jaraee (Universiti Malaysia Sarawak (UNIMAS), 2014)
Leptospirosis is an important zoonotic disease which is caused by Leptospira. Leptospira can infect human from animals, contaminated water and soil. The main objective of this research was to determine the presence of Leptospira in small mammals. The site selected for this research was Bako National Park and the sampling was conducted from 25 until 31 August 2013. The oral and anal swabs were collected from squirrels, rats and bats. The samples collected were enriched in Ellinghausen and McCullough modified by Johnson and Harris (EMJH) media for 30 days at 30°C. After 30 days, the DNA was extracted and the PCR were conducted by targeting lipL32 gene. Overall, one out of 50 samples (2%) showed positive PCR result. The sample was from Giant Muler's Sunda rat. Sundamys muelleri. Hence, the present study showed the possible transmission of small mammals in causing leptospirosis in Sarawak.